Changes in Phospholipid Composition of the Human Cerebellum and Motor Cortex during Normal Ageing - Hancock, Sarah E.; Friedrich, Michael G.; Mitchell, Todd W.; Truscott, Roger J. W.; Else, Paul L. (Nutrients, 2022)
(1) Background: Changes in phospholipid (phosphatidylcholine, phosphatidylethanolamine and phosphatidylserine, i.e., PC, PE and PS) composition with age in the mitochondrial and microsomal membranes of the human cerebellum and motor cortex were examined and compared to previous analyses of the prefrontal cortex, hippocampus and entorhinal cortex. (2) Methods: Nano-electrospray ionization on a hybrid triple quadrupole–linear ion trap mass spectrometer was used to analyse the brain regions of subjects aged 18–104 years. (3) Results: With age, the cerebellum showed many changes in the major phospholipids (>10% of the phospholipid class). In both membrane types, these included increases in PE 18:0_22:6 and PS 18:0_22:6, decreases in PE 18:0_20:4 and PS 18:0_18:1 and an increase in PC 16:0_16:0 (microsomal membrane only). In addition, twenty-one minor phospholipids also changed. In the motor cortex, only ten minor phospholipids changed with age. With age, the acyl composition of the membranes in the cerebellum increased in docosahexaenoic acid (22:6) and decreased in the arachidonic (20:4) and adrenic (22:4) acids. A comparison of phospholipid changes in the cerebellum, motor cortex and other brain areas is provided. (4) Conclusions: The cerebellum is exceptional in the large number of major phospholipids that undergo changes (with consequential changes in acyl composition) with age, whereas the motor cortex is highly resistant to change.